Salt intake determines retinal arteriolar structure in treatment resistant hypertension independent of blood pressure - Raff, Ulrike; Harazny, Joanna M.; Titze, Stephanie; Schmidt, Bernhard Magnus Wilhelm; Michelson, Georg; Schmieder, Roland (Atherosclerosis, 2012)
Patients with treatment resistant hypertension are at increased risk of developing cardiovascular end organ damage. The role of sodium in end organ damage is gaining interest and an independent association of sodium and cardiovascular morbidity and mortality has been described.In an observational study including 40 patients with treatment resistant hypertension, we analysed retinal arteriolar structure in vivo as a determinant of remodelling of small resistant vessels (wall/lumen ratio, wall thickness, wall cross section area) using scanning laser Doppler flowmetry and automatic full-field perfusion imaging analysis. Urinary sodium excretion was determined by 24h urine sample and, in parallel 24h ambulatory blood pressure was measured. We analysed the association of the retinal arterial structure with urinary sodium excretion and blood pressure.Wall to lumen ratio, wall thickness and wall cross section area were strongly associated with urinary sodium excretion but not with 24h blood pressure. In a multiple regression analysis including urinary sodium excretion, BMI, age and 24h blood pressure, urinary sodium excretion emerged as the only independent determinant of wall thickness (?=0.432, p=0.01), and wall cross section area (?=0.439, p=0.008).Our results clearly demonstrate that salt intake influences the structure of retinal arterioles independent of blood pressure in treatment resistant hypertension. Considering the morphologic relation of retinal arteriolar and cerebral vascular structure these results might prove to have important implications on risk stratification in patients with treatment resistant hypertension.
EVALuna2:3574